Al Ababeed : filmer Zénobie comme une héroïne nationale - Thomas Richard (Frontière·s)
The Syrian television programme Al Ababeed, broadcast in 1997, follows the events that led to the fall of Palmyra and the end of Zenobia's power. Produced with considerable resources, it was a milestone in the transformation of Zenobia into a national myth. Through its aeastethic research, it aims to flesh out this myth by idealising Palmyrene society, while at the same time making it emotionally accessible to a contemporary audience. The aim of the show, which is designed according to the imperatives of the Syrian regime, is to use the plasticity of the myth to develop a narrative about contemporary Syria and Palestine built around a national symbol of unity, thus transforming the show into a topical political object.